Der Einfluss der Mosaiken des vorderen Orients auf hispanische Mosaiken am Ende der Antike - BLÁZQUEZ MARTÍNEZ, José María (Journal of Mosaic Research, 2009)
The article discusses the influx of oriental mosaics in Hispania at the end of the Antiquity. Preference of geometric decoration and representations of abstract ideas are the main indications of this influence. Two possible reasons for this phenomenon are either oriental artists who came to Hispania or copy-books which spread oriental motifs in this region. (IIL) Se estudia el influjo de los mosaicos del Oriente en algunos mosaicos hispanos con decoración geométrica, mitológica y alegórica, de época imperial, del final de la Antigüedad y paleocristianos.
p. 7-31, 20 ill. n.b., 8 coul.
Keywords: Études générales sur la mosaïque; Allégorie; Chrétien (art, culture, société); Décor figuré; Décor géométrique; Influence; Mythologie, mythologique (scène); Orient; Proche Orient